Bedlam - Kennen, Ally (Marion Lloyd London, 2014)
Once the ruin in the forest was a lunatic asylum. Now it's deserted. Or is it? When 16-year-old Lexi stays at her mother's country house, she is woken by the midnight howling. Dogs are disappearing from the village. Is a forgotten inmate haunting the derelict mansion? Lexi is about to uncover the shocking truth..